Pembelajaran Matematika Berbasis Konsep dalam Meningkatkan Kompetensi Siswa dan Mahasiswa: Tinjauan Literatur Sistematis - Anjarwati Anjarwati (FKIP Universitas Mataram, 2026)
The objectives of this study were to: 1) Identify the role of concept-based mathematics learning in improving student competencies; 2) Identify factors that influence concept-based mathematics learning; 3) Identify competencies that are influenced by concept-based understanding. This research reviewed 15 from 507 articles in 2014-2024 from the Google Scholar, Scopus database and Sinta 1 indexed national journals. The result of this study is that concept-based mathematics learning can systematically improve students' mathematical competence. The findings of factors that influence concept-based mathematics learning are mathematical mindset and concept understanding of teachers, teaching strategies, conceptual knowledge, and assessment and feedback. Furthermore, concept-based knowledge in this literature review can improve long-term retention, meaningful understanding, critical thinking, metacognition, problem solving and self-regulated.